Cálculo de correntes de curto-circuito e ajuste dos relés de proteção em microrredes - Daniel Amaral Pinheiro (2018)
This work presents the development and implementation of a methodology for the calculation of short circuit currents in microgrids, aiming at the application in the protective relays current adjustments. Initially, a bibliographic review is presented, which addresses the international and national legislation used in the installations, distributed generation technologies and energy storage systems, the benefits of the implantation referring to the power quality, reliability and resilience and the main characteristics of the operation and control architectures. Then, the theme of microgrids protection is introduced, where the main characteristics of the interface with the electrical power grid, including the impacts of its connection in the protection system, are detailed. After this, the methodologies present in the literature regarding the short circuit calculation in microgrids are discussed, where their most important characteristics and limitations are analyzed. Based on the theoretical references studied and also the method of superposition of electric circuits, a new methodology is developed to calculate the short circuit currents that occur internally to the microgrids. The superposition of circuits is applied to the sources from synchronous machines and a new calculation method using dynamic matrices is developed for the sources from photovoltaic systems. All the steps involved in the design of the methodology are detailed, including the mathematical equations that govern the system and the implementation of a program to run automatically the calculations. This program is used for simulation in a microgrid architecture proposed and presents good results regarding the calculation of the short circuit currents in the bars and elements of the installation. In the final stage of the work, a graphical interface is developed for the operation and control of the microgrid, where the values of currents obtained in the simulation are used in the adjustment of the points of operation for the protective relays, aiming the coordination and selectivity between them.